Computed Tomography Blush and Splenic Injury: Does it always Require Angioembolization?. Issue 10 (October 2013) - Post, Rebecca; Engel, Delphine; Pham, Jacqueline; Barrios, Cristobal
The implication of splenic contrast blush on computed tomography (CT) in blunt trauma patients and whether it is an indication for angioembolization (AE) remains controversial. Our objective was to determine whether CT blush and its subsequent treatment have any impact on outcomes in blunt trauma patients with low-grade splenic injuries. A retrospective review identified adult patients with splenic injury (American Association for the Surgery of Trauma grades 1 to 3) from blunt abdominal trauma who were evaluated with a CT scan over a 3.5-year period at a Level I trauma center. Patient groups analyzed included: observation patients with no CT blush (n = 110), observation patients with CT blush (n = 18), and AE patients with CT blush (n = 22). Patients with CT blush who were observed did not demonstrate significantly worse outcomes compared with the patients with no CT blush. Additionally, patients with CT blush who underwent AE did not show any significant improvement in outcomes compared with patients who were observed with CT blush. Our study suggests that CT blush does not predict worse outcomes for blunt trauma patients with low-grade splenic injury who underwent observation. Furthermore, AE does not seem to provide any advantage to this subset of patients.